A new species of Grotea (Hymenoptera: Ichneumonidae) in Argentina: systematics and biological notes - Ramello, Pablo J.; Aquino, Daniel A.; Lucia, Mariano (Zootaxa, 2025)
We describe a new species of parasitoid of the bee Ceratina (Crewella) rupestris Holmberg, Grotea coca sp. nov. Images and data on the parasitoid’s life cycle are provided. Also, G. eburnea (Porter) is recorded for the first time in southern Argentina. An identification key is provided for Grotea species present in Argentina.